2019
DOI: 10.3389/fimmu.2019.02879
|View full text |Cite
|
Sign up to set email alerts
|

Genome-Wide CRISPR Screen Reveals Cancer Cell Resistance to NK Cells Induced by NK-Derived IFN-γ

Abstract: The anti-leukemia activity of NK cells helps prevent relapse during hematopoietic stem cell transplantation (HSCT) in leukemia patients. However, the factors that determine the sensitivity or resistance of leukemia cells in the context of NK-mediated cytotoxicity are not well-established. Here, we performed a genome-wide CRISPR screen in the human chronic-myelogenous-leukemia (CML) cell line K562 to identify genes that regulate the vulnerability of leukemia cells to killing by primary human NK cells. The distr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
41
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(48 citation statements)
references
References 29 publications
0
41
0
Order By: Relevance
“…In contrast, in an HBV-associated hepatocellular carcinoma (HCC) model, IFNγ produced by NK cells was found to induce STAT1-dependent expression of epithelial cell adhesion molecules, promoting the epithelial-to-mesenchymal transition of HBV surface antigen-positive hepatocytes and increasing HCC incidence in vivo [ 169 ]. In another study, NK-derived IFNγ-induced the expression of MHC class I molecules in leukemia cells and decreased their susceptibility to NK cytotoxicity [ 170 ], while in melanoma cells loss of IFNγ signaling components increased tumor cell sensitivity to NKs [ 171 ]. Using several mouse tumor models, IFNγ was shown to be essential for CTL-driven development of immune-resistant cancer cell clones through increased tumor cell genetic instability [ 172 ].…”
Section: Effects Of Interferons On the Tumor Microenvironmentmentioning
confidence: 99%
“…In contrast, in an HBV-associated hepatocellular carcinoma (HCC) model, IFNγ produced by NK cells was found to induce STAT1-dependent expression of epithelial cell adhesion molecules, promoting the epithelial-to-mesenchymal transition of HBV surface antigen-positive hepatocytes and increasing HCC incidence in vivo [ 169 ]. In another study, NK-derived IFNγ-induced the expression of MHC class I molecules in leukemia cells and decreased their susceptibility to NK cytotoxicity [ 170 ], while in melanoma cells loss of IFNγ signaling components increased tumor cell sensitivity to NKs [ 171 ]. Using several mouse tumor models, IFNγ was shown to be essential for CTL-driven development of immune-resistant cancer cell clones through increased tumor cell genetic instability [ 172 ].…”
Section: Effects Of Interferons On the Tumor Microenvironmentmentioning
confidence: 99%
“…Altogether, these studies have confirmed key roles for antigen processing and presentation, IFNγ signaling, and the TNF response in antitumor immunity and identified novel members of these pathways that are mutated in patient tumors and may represent new therapeutic avenues for activating the immune response to cancer (Box 3 and Figure 2). These screens have also been extended to additional tumor-immune cell interactions, including with natural killer (NK) cells [54][55][56] and chimeric antigen receptor (CAR) T cells [57]. A significant caveat is that many of these screens have been performed in vitro using two-cell interaction systems, or in immunodeficient in vivo models where exogenous tumor-specific T cells are provided (due to the inherent immunogenicity of CRISPR components in immune-competent mice), which does not account for the complex multicellular interactions that occur during an antitumor immune response.…”
Section: Trends Trends In In Immunology Immunologymentioning
confidence: 99%
“…Another genome-wide CRISPR/Cas9 screen allowed to reveal genes responsible for resistance of human chronic-myelogenous-leukemia cells to NK cells induced by IFN-γ. This process was discovered to be governed by loss of gene encoding a ligand responsible for cytotoxicity, as well as by a gain of function mutation affecting antigen presentation that protects wild type cells [ 55 ]. Nonetheless, IFN-γ-mediated responses are of great concern, limiting ongoing research, due to IFN-γ having both tumorigenic and antitumorigenic characteristics [ 56 ].…”
Section: Chimeric Antigen Receptors (Cars) For Cancer Immunotherapmentioning
confidence: 99%